Factors Affecting Motivation for Career Selection of Public Accountants - Budiandru Budiandru (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2021)
The purpose of this study was to determine the influence of intrinsic value, work environment, and job market considerations on the motivation to choose a career as a public accountant either partially or simultaneously. This research method uses multiple linear regression analysis with a sample of 210 students of the faculty of economics and Business, University of Muhammadiyah Prof. Dr. Hamka. The research results based on the t-test show that the intrinsic value of work affects the motivation for choosing a career to become a public accountant, while the work environment and job market considerations do not affect the motivation for choosing a career to become a public accountant. Simultaneously, the intrinsic value of work, work environment, and labor market considerations affect the motivation to choose a career to become a public accountant. Public accounting firms need to consider workspace and freedom for auditors to complete existing work, providing intellectual challenges with a dynamic work atmosphere.